First Principles Computation of Electronic Structure and Dynamical Properties of Perovskite LaBa2Cu3O7 - Phillip, Otieno Nyawere; Peter, Tanui; Cherotich, Seville (Kabarak Journal of Research & Innovation, 2025)
Perovskite materials have attracted research because of their ability to transition from normal metals to superconductors. This study reports electronic structure and dynamical properties of LaBa2Cu3O7 perovskite carried out in the framework of density functional theory (DFT) using the Quantum espresso code. This is based on plane wave self-consistent field (PWscf) and ultrasoft pseudopotential (USPP) method as treated in the Perdew-Burke-Ernzerhof (PBE) generalized gradient approximation and local density approximations as implemented in Quantum Espresso Code. The electronic structure uncovers essential aspects such as bandgaps, Fermi surfaces, and density of states, offering valuable insights into the material's behaviour. Under structural properties, optimization of the material’s cell dimensions, lattice parameters, k-points, and the kinetic energy cut-off values were properly checked through graphing and accurate values were obtained at the convergence of the ground state energy at minimum convergence threshold. Band structures of LaBa2Cu3O7 are similar to that of superconducting perovskites. The results show that LaBa2Cu3O7 is orthorhombic structure with lattice parameter calculated to be 3.925 Å which compares well with other works and a band gap of 2.043eV. The valence band is typically dominated by O 2p states, while the conduction band involves Cu 3d states. Phonon calculations shows that the compound is dynamically stable as there are no negative frequencies observed.
Keywords: Dynamical; Electronic; Perovskite Structure